Controlled randomised trial of visual biofeedback versus muscle training without a visual display for intractable constipation. - Koutsomanis, D (1995)
Training to contract the abdominal muscles effectively and to relax the pelvic floor during defecation straining helps some patients with severe constipation. Hitherto all such training has used a visible or audible signal of sphincter muscle activity as a biofeedback method to assist in relaxation. A randomised controlled trial comparing the outcome of muscular training without any biofeedback device with the same training supplemented by an electromyographic (EMG) record visible to the patient is reported. Significant symptomatic improvement was noted and electromyographic measurements confirmed a decrease in pelvic floor muscle activity during defecation straining after treatment in both groups. The outcome was similar in the two treatment groups. Muscular coordination training using personal instruction and encouragement without a visual display is thus a potentially successful treatment suitable for outpatient use by paramedical personnel.